VALIDASI KEWACANAAN ADUAN KASUS UJARAN KEBENCIAN DI WILAYAH HUKUM POLRI RESOR TEBO, JAMBI TAHUN 2019 (Discourse Validation of Cases Complaint of Hate Speech in the Jurisdiction of Police Precinct of Tebo Regency in Jambi Province 2019) - Natal P. Sitanggang (SAWERIGADING, 2020)
This paper aims to describe one of the validation processes of a criminal offense of hate speech in the police resort jurisdiction in Jambi province in 2019. The data was obtained from the text of the report presented in the police investigation report. The main problem in this paper is the validity of the complainant’s complaint from the linguistic perspective. At the initial processing method, the text was reconstructed into conversation texts to see the conversation flow, proportions, and propositions in each utterance units. Next, the utterance units were analyzed on pragmatics discourse studies. It involves speech act theory, performative illocution, and interpersonal rhetoric (a means-end schema). The result shows that the criminal complaint of a complainant is valid as an insulting form. In addition, there is also a threatening form as other criminal elements. However, it is not considered a complainant’s criminal complaint, and it is recommended not to be involved in the legal process. AbstrakPenelitian ini bersifat kualitatif yang bertujuan untuk mendeskripsikan salah satu proses validitas delik aduan pidana ujaran kebencian di wilayah hukum salah satu resor kepolisian di Provinsi Jambi tahun 2019. Data bersumber dari teks laporan yang diterakan dalam naskah berita acara pemeriksaan (BAP). Masalah utama dalam makalah ini adalah perihal validitas aduan pelapor dari sudut pandang kebahasaan. Metode pengolahannya pada tahap awal, teks tersebut direkonstruksikan menjadi teks percakapan untuk melihat alur percakapan, proporsi, dan proposisi setiap satuan ujaran. Selanjutnya, rangkaian unit-unit ujaran itu dianalisis berdasarkan kajian wacana pragmatik yang melibatkan teori tindak tutur, ilokusi performatif, dan retorik interpersonal (skema means-end). Hasilnya menunjukkan bahwa delik aduan pelapor valid sebagai bentuk penghinaan. Selain itu, terdapat juga unsur pidana lain yaitu pengancaman. Namun, pengancaman ini bukan sebagai delik aduan pelapor dan disarankan untuk diabaikan dalam proses hukum.